Vampire Capitalism : Fractured Societies and Alternative Futures - Kennedy, Paul (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This book argues that in recent decades an unrestrained vampire-capitalism has emerged, disengaged from the needs of citizens and workers, leading to a deepening of social class, generational, gender, educational and ethnic divisions. The author explores how our cultural obsession with self-realization undermines our capacity for collective action and ability to confront threats such as climate change and the impact of the rapid advance of technology on labour. Drawing on sociology and political economy as well as worldwide case studies, the chapters interrogate how we arrived at these dilemmas and how we might escape them through establishing alternative social economies. Vampire Capitalism will be of interest to students and scholars across a range of disciplines, including sociology, social theory, globalisation studies, development studies, political economy, geography, politics and social policy.- Resumé vydavatel
Keywords: kapitalismus; hospodářské systémy; sociální struktura; sociální nerovnost; capitalism; economic systems; social structure; social inequality; elektronické knihy; monografie; electronic books; monographs